Shoreline armor removal can restore variability in intertidal ecosystems. (July 2022) - Des Roches, Simone; LaFuente, Juhi R.; Faulkner, Hannah S.; Morgan, Jason R.; Perla, Bianca S.; Metler, Maria; Dethier, Megan N.; Toft, Jason D.
Graphical abstract: Highlights: Humans modify marine nearshore ecosystems through shoreline armoring such as seawalls. Past work shows that armor reduces mean beach wrack, log, and invertebrate abundance. New volunteer-collected data show that armor also reduces variance of these responses. Shores with no history of armor are more variable among sites, but also across time. Restoration through armor removal can recover this spatial and temporal variability. Abstract: Humans have drastically modified marine nearshore ecosystems through shoreline armoring. Armor, in the form of seawalls and bulkheads, reduces the mean abundance of key ecological features of shoreline ecosystems, such as the amount of beach wrack, the number of beached logs, and the density of supratidal invertebrates. Armor also affects the physical and biological composition and diversity of these important ecological responses – altering the makeup of beach wrack and invertebrate species, for example. Less is known, however, about changes in variability – both over time and space – of ecological responses across natural, restored, and armored shores. Temporal and spatial variation in physical and biological variables can themselves be indicators of ecosystem health and effectiveness of restoration. Working alongside community (citizen) scientists, we found that beach wrack (a nutrient and habitat resource), logs (an element of habitat structure), and supratidal invertebrates (part of the consumer community) often increased following restoration. Further, not only were wrack, logs, and invertebrates on average more abundant and diverse at natural (never armored) shore types compared to armored shore types, but they also frequently had higher variance. In many cases, variance of ecological responses in restored shore types were more similar to natural shore types than armored shore types, indicating a positive effect of restoration. We found that differences among sample sites, rather than across sample years, explained more of the variation in ecological responses across all shore types. Because shoreline armoring is a pervasive human activity, public perception of this variability is key to the social context of restoration success. Participation in data collection through community science endeavors is one way to encourage an appreciation for natural variability within and across landscapes. We implore that shoreline monitoring efforts should evaluate and communicate ecosystem variability as a key indicator of restoration success.